Effects of melatonin treatment on twin pregnancy and fetal mortality in sheep - Lakatos, Gy.; Vincze, B.N.; Vass, N.; Dobos, A. (Polish Journal of Veterinary Sciences, 2026)
This study is the first to examine the effects of melatonin implants on the litter size and fetal mortality rate of Blanc du Massif Central ewes in Hungary. The ewes were divided into two experimental groups: group A: 96 ewes were treated with melatonin implants and group B: 114 ewes was the control group. The number of twin litters was significantly larger in group A than in group B, whereas the fetal mortality rate was significantly lower in the melatonin treated group than in the control group. These findings suggest that melatonin implants may provide significant benefits for sheep production in continental regions; however, their application requires careful consideration due to potential adverse effects on flock management associated with an increased incidence of twin pregnancies.